"São Marcos" e "Sarapalha", de João Guimarães Rosa, à luz da arquitetônica bakhtniana - Tacito, Gilmara Alonso (2010)
The objective of this dissertation is to investigate the presence of the Author Creator entity interacting with characters in narratives "São Marcos" and "Sarapalha" (1946), Sagarana (1946), written by João Guimarães Rosa (1908- 1967). Concerning to the assumptions of the aesthetic material of Mikhail Bakhtin, it is understood that there is no linkage between work and life of the author, whereas popular culture connects the study of the literary work to the writer's life, only to listen to his voice, pointed to confidences. For the author, all aesthetic analysis should not be targeted directly to the work, but about what the work represents for the aesthetic activity of the artist and the reader. Our object here is delineated as the stuffing of this aesthetic activity focused on the literary work: the aesthetic object. This is the dual-perspective, here, applied to the reading of Rosa's narrative: reading the aesthetic object in its singularity and artistic structure called aesthetic architectonic object, design that allows to the Author Person (ethical-social element) unfolded in Author Creator (constitutive element of the artistic form). This compositional unity is realized between the consciousness of the Author Creator and the outside world resulting from an architectonic model of the human psyche, that makes the world (otherness) your utterance, and, in it, his conscience: with this focus we claim to read the "stranger" in Guimarães Rosa. That is, to read the artistic form as an event or achievement. The reading methodology applied in this study is also based on the concept of the aesthetic object, by practicing discrimination and isolation of the analytical material deductive of the usual perception to the unusual artistic literary form of both tales from Sagarana, in their specific critical-interpretation. The theoretical background is Mikhail Bakhtin, and supporting concepts applied to the analysis, and interpretation, pointing to: Tzvetan Todorov; Katerina Clark & Michael Holquist; Roland Barthes; Antonio Candido; Massaud Moises; Carlos Alberto Faraco; Marília Amorim; Renata Coelho Marchezan